Safety and efficacy of Levorag emulgel in the treatment of anal fissures using a validated scoring system - Tomasicchio, G; Dezi, A; Picciariello, A; Altomare, D. F; Giove, C; Martines, G; De Fazio, M; Rinaldi, M (Frontiers in Surgery, 2023)
Introduction Anal fissure is one of the most common anal disease characterized by intense anal pain, and deterioration of patients quality of life. Treatment is mainly based on the topical administration of calcium antagonist or nitric oxide ointments, and in cases refractory to medical treatment patients can undergo surgery. This study aims to assess the efficacy and safety of Levorag emulgel in the treatment of acute and chronic fissures using of a validated scoring system. Material and Methods A prospective observational study was carried out on patients with anal fissures between February and May 2022. The efficacy of the treatment was evaluated using the REALISE score, a new validated scoring system that rates VAS for pain, NSAID use, pain duration, bleeding, and quality of life (QoL), recorded after 10, 20 and 30 days from the beginning of treatment. Results Forty patients (median age 46 years, IQR 29-57, 70% women) with acute (22, 55%) or chronic (18, 45%) anal fissures entered the study. The median anal pain score according to the VAS scale decreased significantly from 7 (IQR 4.7-8) at baseline to 1 (IQR 0-3.2, p=0.05) after 20 days. At the 30-day proctological examination, 22 patients (61%) were pain free (median VAS of 0, IQR 0-1.2, p<0.05). Pain duration after defecation measured according to the REALISE score, showed a significant decrease after 10 days, from a median value of 2 (IQR 1-4) to 1 (IQR 1-1.2) (p<0.005). The median value of the REALISE score decreased significantly, from 15 (IQR 11-19.25) at first proctological evaluation to 4 (IQR 4-6, p=0.139) after 30 days of treatment. At day 30, complete fissure healing was achieved in 30 patients (80%). The healing rate was 82% and 78% in patients with acute and chronic anal fissures, respectively. Conclusion The use of Levorag® Emulgel may represent a safe and effective non-invasive first line treatment in patients affected by acute or chronic anal fissure.